2021
DOI: 10.1097/md.0000000000024821
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception of online learning during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has disrupted teaching in a variety of institutions, especially in medical schools. Electronic learning (e-learning) became the core method of teaching the curriculum during the pandemic. After 8 weeks of only online learning, a survey was conducted to investigate perception of this type of learning among medical students. A survey was conducted by distributing an online questionnaire to Polish medical students. Data gathered from the survey were analyzed with routine statisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
407
8
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(489 citation statements)
references
References 25 publications
51
407
8
23
Order By: Relevance
“…Regarding the positive aspects of e-learning, the research has shown that students are particularly pragmatic, considering time-saving as the main advantage, closely followed by the comfort offered by staying home, as well as the accessibility provided by the online environment. The same positive results, such as the possibility to stay at home, the friendly environment at home, and the possibility to have access to online materials were observed in a study conducted with Polish medical students [46]. These advantages could help create courses that fit the needs of certain categories of students (those who work, who are unable to attend courses, who cannot afford to study in another city, etc.).…”
Section: Discussionsupporting
confidence: 53%
“…Regarding the positive aspects of e-learning, the research has shown that students are particularly pragmatic, considering time-saving as the main advantage, closely followed by the comfort offered by staying home, as well as the accessibility provided by the online environment. The same positive results, such as the possibility to stay at home, the friendly environment at home, and the possibility to have access to online materials were observed in a study conducted with Polish medical students [46]. These advantages could help create courses that fit the needs of certain categories of students (those who work, who are unable to attend courses, who cannot afford to study in another city, etc.).…”
Section: Discussionsupporting
confidence: 53%
“…During our research, study participants showed also an optimistic and general appreciation of the advantages that the online learning transition brought to the quality of their educational life in terms of time, access, less traveling, reduced cost of accommodation and transportation in other settings; moreover, it appeared that online learning materials were also delivered faster (Bączek et al, 2021). A new aspect, enabling the educational life, explored by students was the discovery of the advantages of new media of communication gained from the online setting, like the faster response and contact with teachers and tutors, fewer time boundaries and generally the sense of continuous and available connection with fellow students (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…They expressed initial concerns about missing the chance to observe and to be physically in the class, to interact, ask questions, or follow other students' reasoning, which for some of them is also an element of facilitation of learning and quality of educational life (Fawns et al, 2019). The missing interaction interpreted as missing the embodiment of the educational experience was a topic highlighted in the interviews by students attending courses with less theoretical programs, like intensive care specializing courses (Bączek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the implementation of virtual consultations with simulated patients may be an alternative measure to tackle this problem. Virtual patients and simulation of real-life clinical scenarios may enable the learner to prepare him/herself before a real patient encounter [ 5 , 14 ]. The creation of online components promotes well-structured courses and can help students in distributing their studies throughout the term, thus suggesting enhanced learning [ 15 ].…”
Section: Discussionmentioning
confidence: 99%